(untitled) (ETIMA, 2024)
Electrosurgery is a good alternative to the scalpel or lasers for soft tissue management and would be the method of choice. Oral electrosurgery is widely accepted throughout the world and has a broad spectrum of clinical applications. Once the clinician understands the nature of the different waveforms and how electrosurgical technology relates to clinical results, a comfort level will be achieved making clinical applications safe, predictable and easy. Electrosurgery can be used instead of the scalpel to cut soft tissues, with the goal of reducing hemorrhage. Electrosurgery alludes to the delivery of thermal energy in the form of an alternating current in the radiofrequency range from an electrical generator to the probe tip and the tissues. The heat generated in the tissue depends on the current intensity, the distance from this tissue to the electrode tip, and the period during which the RF energy is delivered. Electrosurgery is the passage of high frequency radio waves (RF energy) into soft tissue resulting in a variety of clinical effects, including cutting, cutting and coagulation at the same time, coagulation or tissue destruction. Because of the resistance offered by the tissue to the incoming RF energy, the tissue heats up. The electrode tip never gets hot. In actuality, the water in the cells is boiled causing the cells to explode. Radiosurgery has also become an unofficial but accepted term referring to electrosurgery instruments that fall into the higher frequency range of 3-4 mHz (3-4 million cycles per second). Study by Maness et al. in 1978 concluded that higher frequency electrosurgical units produce less tissue alteration than those instruments with frequencies under 2 mHz. Higher frequency units produce less lateral heat and, therefore, less tissue alteration. The optimal frequency appears to be in the 3-4 mHz range. There are numerous indications for oral electrosurgery and some include bleeding control, cosmetic elongation of clinical crowns, soft tissue management during crown and bridge procedures, biopsies, frenectomies, pulpotomies, collecting tissue for gingival grafts, incisions or excisions and tissue contouring. The main goal of this study is to highlight the principles and benefits of electrosurgery application. Electrosurgery can never completely replace the scalpel, but it requires more knowledge, skill and complete understanding of the biophysical aspects of the interaction of electrosurgical energy and tissue. Continued research into the field of tissue interaction is promised and potential development of applications of electrosurgery.